Cardiovascular Lifetime Risk Predicts Incidence of Coronary Calcification in Individuals With Low Short‐Term Risk: The Dallas Heart Study - Paixao, Andre R. M. (J Am Heart Assoc, 2014)
BACKGROUND: The absence of coronary artery calcium (CAC) in middle age is associated with very low short‐term risk for coronary events. However, the long‐term implications of a CAC score of 0 are uncertain, particularly among individuals with high cardiovascular lifetime risk. We sought to characterize the association between predicted lifetime risk and incident CAC among individuals with low short‐term risk. METHODS AND RESULTS: We included 754 Dallas Heart Study participants with serial CAC scans (6.9 years apart) and both low short‐term risk and baseline CAC=0. Lifetime risk for cardiovascular disease was estimated according to risk factor burden. Among this group, 365 individuals (48.4%) were at low lifetime risk and 389 (51.6%) at high lifetime risk. High lifetime risk was associated with higher annualized CAC incidence (4.2% versus 2.7%; P < 0.001). Similarly, mean follow‐up CAC scores were higher among participants with high lifetime risk (7.8 versus 2.4 Agatston units). After adjustment for age, sex, and race, high lifetime risk remained independently associated with incident CAC (OR 1.60; 95% CI 1.12 to 2.27; P=0.01). When assessing risk factor burden at the follow‐up visit, 66.7% of CAC incidence observed in the low lifetime risk group occurred among individuals reclassified to a higher short‐ or long‐term risk category. CONCLUSION: Among individuals with low short‐term risk and CAC scores of 0, high lifetime risk is associated with a higher incidence of CAC. These findings highlight the importance of lifetime risk even among individuals with very low short‐term risk.